The malalignment syndrome diagnosing and treating a common cause of acute and chronic pelvic, limb and back pain - Schamberger, Wolf (Churchill Livingstone, 2013)
Lack of appreciation and knowledge of the malalignment syndrome often leads to a failure to notice the possible aetiological or predisposing factors contributing to many musculoskeletal problems. This title provides a detailed description of this syndrome and how it can be identified and treated.